Games for Social Learning on (Ground) Water Governance Interactive session for World Bank SAR Regional Retreat - Meinzen-Dick, Ruth S.; Zhang, Wei; ElDidi, Hagar (2023)
Meinzen-Dick, R., W. Zhang, and H. ElDidi. 2023. Games for Social Learning on (Ground) Water Governance. PowerPoint presentation during the interactive session for World Bank South Asia Region Regional Retreat, World Bank, USA. March 6, 2023